2022
DOI: 10.1186/s12912-022-01093-9
|View full text |Cite
|
Sign up to set email alerts
|

Clinical nurses’ moral courage and related factors: an empowerment perspective

Abstract: Background Moral courage as part of the moral competence of nurses has received increasing attention. Determination of the factors affecting moral courage is important in improving the quality of care. The purpose of this study was to investigate moral courage and related factors among frontline nurses from an empowerment perspective. Methods A cross-sectional study was conducted using data collection instruments comprising four main parts: the sel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 19 publications
(8 citation statements)
references
References 33 publications
1
7
0
Order By: Relevance
“…00), which was in the middle and upper level compared with the average score of the scale (52. 5); consistent with the findings of this study, other studies have shown that nurses, especially in central China and Finland, have reported high moral courage (Hu et al, 2022;Kleemola et al, 2020).…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…00), which was in the middle and upper level compared with the average score of the scale (52. 5); consistent with the findings of this study, other studies have shown that nurses, especially in central China and Finland, have reported high moral courage (Hu et al, 2022;Kleemola et al, 2020).…”
Section: Discussionsupporting
confidence: 92%
“…The organization can establish a virtuous loop and boost moral courage when these actions are permitted and affirmed by the organization (Pajakoski et al, 2021). (Hu et al, 2022).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Considerable empirical research has been conducted to better understand nurses' moral courage and how to support them under complex ethical challenges. Previous cross‐sectional studies have explored the relationship among nurses (Gibson et al., 2020 ; Hauhio et al., 2021 ; Hu et al., 2022 ; Peng et al., 2023 ; Wenwen et al., 2018 ). One study demonstrated that the mean score for moral courage among nurses working in ICUs in COVID‐19 pandemic hospitals was 82.08 (Goktas et al., 2023 ).…”
Section: Discussionmentioning
confidence: 99%
“…A moral perspective is implicit in all nursing activities since ethical problems are a component of daily nursing practice (Thompson et al., 2006 ). There has been a growing focus on nurses' moral courage as a component of their moral competence (Hu et al., 2022 ). In the field of nursing, moral courage is defined as a nurse's adherence to their professional code of ethics and strict adherence to these guidelines, even if such adherence has a foreseeable or real negative impact on them (Numminen et al., 2017 ).…”
Section: Introductionmentioning
confidence: 99%